87.8k views
0 votes
Question is in the image

Question is in the image-example-1
User Kenneth Li
by
4.9k points

2 Answers

4 votes

Answer:

y=(-2/3)x^2

Step-by-step explanation:

User Sarath Chandra
by
5.4k points
4 votes

Answer: g(x) = (-2/3)x^2

=====================================================

Step-by-step explanation:

The blue parent function has a positive coefficient of 1. The purple g(x) function is a reflection of f(x) over the x axis, so everything is now negative. The coefficient must be negative as well.

But the answer is simply not g(x) = -x^2 because plugging x = 3 does not lead to y = -6 as the point (3,-6) shows.

Let's say the coefficient is k for now. So we have y = kx^2

Plug in x = 3 and y = -6. Solve for k

y = kx^2

-6 = k(3)^2

-6 = k*9

9k = -6

k = -6/9

k = -2/3

So we update y = kx^2 into y = (-2/3)x^2

Meaning that g(x) = (-2/3)x^2 is the equation of the purple curve.

Plug x = 3 into g(x) to find that

g(x) = (-2/3)x^2

g(3) = (-2/3)(3)^2

g(3) = (-2/3)(9)

g(3) = -6

which is the output we want, so this confirms we have the correct coefficient.

User Mmw
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.